A runner modernization in a Deriaz turbine hydropower station. Issue 2 (March 2019) - Kikuta, H; Suzuki, R; Nakamura, S; Anciger, D
Abstract: This paper introduces our experience of a Deriaz turbine modernization project. N hydropower station in Japan, with the 50MW Deriaz turbine (turbine mode only), had been operated for approximately 50 years. Not only for the purpose of the maintenance but also for the energy production increase, the turbine modernization was planned along with the scheduled overhaul. The modernization scope of the hydraulic parts was discussed and the blade only option was selected. In the new blade development, the existing mechanical limits were the restriction and the lack of recent experiences in Deriaz turbine development was a challenge. For the challenge, a development procedure special for the project was introduced, using state of the art CFD technology and the model test. As the result, within the existing mechanical limits, 3% gain in performance at the full load has been achieved and the performance was successfully confirmed in the model test and the prototype site test.